2011
DOI: 10.1248/bpb.34.146
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Synthase Kinase-3.BETA.2 Has Lower Phosphorylation Activity to Tau than Glycogen Synthase Kinase-3.BETA.1

Abstract: Glycogen synthase kinase-3b (GSK-3b) is a serine/threonine kinase that is involved in the regulation of many signaling pathways in vertebrates.1-3) GSK-3b is expressed in two splice variants. GSK-3b1 (the short form of GSK-3b) ubiquitously distributes in organs. In contrast, GSK-3b2 (the long form of GSK-3b), whose structural difference is the only 13 amino acids insert at the C-terminal side of the catalytic site, is present in central nervous system. 4,5) Although, so far, many researches on GSK-3b are conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…For example, Ser396 in tau is phosphorylated by both splice variants, whereas Ser199 is a significant target of GSK-3 β 1, but not of GSK-3 β 2 activity. It has recently been suggested that the interaction of GSK-3 β 2 with tau is weaker than that of GSK-3 β 1 [76]. Taken together, these results suggest that, not only are there differential activities of GSK-3 α and GSK-3 β towards tau, there are also partially overlapping, but distinct, tau phosphorylation sites recognised by each of the two isoforms of GSK-3 β [7477].…”
Section: In Vitro Phosphorylation Of Tau By Gsk-3mentioning
confidence: 80%
See 1 more Smart Citation
“…For example, Ser396 in tau is phosphorylated by both splice variants, whereas Ser199 is a significant target of GSK-3 β 1, but not of GSK-3 β 2 activity. It has recently been suggested that the interaction of GSK-3 β 2 with tau is weaker than that of GSK-3 β 1 [76]. Taken together, these results suggest that, not only are there differential activities of GSK-3 α and GSK-3 β towards tau, there are also partially overlapping, but distinct, tau phosphorylation sites recognised by each of the two isoforms of GSK-3 β [7477].…”
Section: In Vitro Phosphorylation Of Tau By Gsk-3mentioning
confidence: 80%
“…There is also a difference in the kinetics and sites of tau phosphorylation induced by the two GSK-3 β isoforms, with GSK-3 β 2 appearing to phosphorylate tau more slowly than GSK-3 β 1 and on different, with some overlapping, tau residues, even under conditions in which other GSK-3 β substrates, such as amyloid precursor protein, are phosphorylated equally [75, 76]. For example, Ser396 in tau is phosphorylated by both splice variants, whereas Ser199 is a significant target of GSK-3 β 1, but not of GSK-3 β 2 activity.…”
Section: In Vitro Phosphorylation Of Tau By Gsk-3mentioning
confidence: 99%
“…After neuronal cell death, intracellular NFTs are released into the extracellular space (Dickson et al, 1992). Interestingly, growing evidence indicates that hyperphosphorylated tau activates GSK-3β through an increase in oxidative stress, neuroinflammation, and apoptosis (Saeki et al, 2011). In addition, GSK-3β impairs lysosomal acidification, a process that entails an inadequate clearance of non-functional proteins (Avrahami et al, 2013).…”
Section: Gsk-3β As a Molecular Link Between Aβ And Taumentioning
confidence: 99%
“…GSK-3, strikingly different behavior to other protein kinases, is active in the resting state [34]. The most well defined mechanism of GSK-3 regulation is the phosphorylation of Serine 9 (Ser9) in GSK-3 and Ser21 in the GSK-3 isoform [35].…”
Section: Regulation Of Gsk-3mentioning
confidence: 99%